2002
DOI: 10.1074/jbc.m109874200
|View full text |Cite
|
Sign up to set email alerts
|

Trialysin, a Novel Pore-forming Protein from Saliva of Hematophagous Insects Activated by Limited Proteolysis

Abstract: We have characterized a pore-forming lytic protein from the saliva of the hematophagous insect Triatoma infestans, a vector of Chagas disease. This protein, named trialysin, has 22 kDa and is present in the saliva at about 200 g/ml. Purified trialysin forms voltage-dependent channels in planar lipid bilayers with conductance of 880 ؎ 40 pS. It lyses protozoan parasites and bacteria indicating that it has a role in the control of microorganism growth in the salivary glands. At higher concentrations, but below t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
97
0
1

Year Published

2005
2005
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 81 publications
(99 citation statements)
references
References 45 publications
1
97
0
1
Order By: Relevance
“…They concluded that T. infestans, which is refractory to infection by T. rangeli, appears to contain a much wider distribution of agglutinins and trypanolytic factors in its tissue than the susceptible species, R. prolixus. Amino et al (2002) characterized a pore-forming lytic protein from the saliva of T. infestans. This protein, named trialysin, lysed protozoan parasites and bacteria indicating that it plays a role in the control of microorganism growth in the salivary glands.…”
Section: Trypanosoma Rangeli and Hemolymph Interactionsmentioning
confidence: 99%
“…They concluded that T. infestans, which is refractory to infection by T. rangeli, appears to contain a much wider distribution of agglutinins and trypanolytic factors in its tissue than the susceptible species, R. prolixus. Amino et al (2002) characterized a pore-forming lytic protein from the saliva of T. infestans. This protein, named trialysin, lysed protozoan parasites and bacteria indicating that it plays a role in the control of microorganism growth in the salivary glands.…”
Section: Trypanosoma Rangeli and Hemolymph Interactionsmentioning
confidence: 99%
“…A lytic protein called "trialysin" has been detected in Triatoma infestans saliva which acts on T. cruzi trypomastigotes (Amino et al 2002). An antimicrobial peptide belonging to the family of small cationic peptides associated with innate immunity has been isolated from the R. prolixus hemolymph (López et al 2003).…”
mentioning
confidence: 99%
“…Other peptides or proteins have also been found which are constitutively present in the hemolymph or different insect secretions, such as an antimicrobial peptide "stomoxyn" detected in Stomoxis calcitrans presenting lytic activity against T. brucei rhodesiense (Boulanger et al 2002a, b). A lytic protein called "trialysin" has been detected in Triatoma infestans saliva which acts on T. cruzi trypomastigotes (Amino et al 2002). An antimicrobial peptide belonging to the family of small cationic peptides associated with innate immunity has been isolated from the R. prolixus hemolymph (López et al 2003).…”
mentioning
confidence: 99%
“…Among our studies, we have characterized a 22 kD pore forming protein, named trialysin, from saliva of T. infestans (Amino et al 2002). This protein contains on the N-terminus a sequence that predicts an amphipathic α-helix and its corresponding synthetic peptide retains cytolytic activity.…”
Section: Structure and Function Of Triatoma Infestans Proteinsmentioning
confidence: 99%